Energy Tunneling Behavior in Geometrically Separated Wave Guides - Omar, M.; Ramzan, R.; Saddiqui, O. F. (Advanced Electromagnetics, 2017)
In this paper, characteristics of energy tunneling channel between the waveguides geometrically separated by a coaxial cable are studied. The novel aspect of design is use of coaxial channel to connect the waveguides while maintaining the energy tunneling phenomena. As anticipated the tunneling frequency depends upon the length of wire inside the waveguide and the length of the coaxial cable. The tunneling frequency also depends upon the dielectric constant of the material inside the waveguide and coaxial cable. At tunneling frequency the field strength (E and H) in the channel is extremely high, making the channel extremely sensitive to small change in permittivity of dielectric occupying the channel. The advantage of the proposed design is, its ability to tune to desired tunneling frequency just by changing the length of the coaxial cable without the need to redesign the waveguide height to accommodate the long tunneling wires. This structure can be used as dielectric sensor both for solid or liquid dielectrics just by placing the sample in coaxial cable cavity, contrary to previously report work where the sample has to be placed inside the waveguide.